Ghana : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria-Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report, 2012)
Ghana's macroeconomic outlook is positive, and the medium-term policy stance is appropriate. On the fiscal side, the government plans to scale up infrastructure investment and further boost revenues. A revised debt sustainability analysis suggests scope for higher nonconcessional borrowing, provided fiscal targets are achieved. The banking sector remains adequately capitalized and liquid, and reform priorities include reducing nonperforming loans and strengthening banks' risk management practices. Program risks arise from external and domestic sources.